(untitled) (Journal of Informatics Education and Research, 2026)
The evolution of rural banking systems remains central to the discourse on inclusive economic development in emerging economies, particularly in countries such as India, where rural populations continue to constitute a significant share of the national demographic and productive workforce. Despite substantial policy interventions, technological advancements, and financial inclusion initiatives introduced over the past decade, rural credit accessibility continues to face structural, institutional, and socio-economic constraints. This study, titled “Rural Credit Accessibility and Banking Sustainability in Emerging Indian Economies: Insights from Nashik (2026)”, critically examines the accessibility of rural credit facilities and evaluates the long-term sustainability of rural banking institutions in the Nashik region of Maharashtra. The research adopts a mixed-method analytical framework integrating quantitative survey analysis with qualitative institutional assessment to investigate the major determinants affecting rural banking outreach, agricultural financing, microenterprise credit flow, digital banking adoption, and borrower trust in financial institutions. Data collected from rural households, cooperative banks, regional rural banks, self-help groups, and banking professionals reveal that although banking penetration has increased significantly due to digital infrastructure and government-led financial inclusion programs, substantial disparities persist in credit accessibility, financial literacy, procedural transparency, and technological adaptability among rural populations.